Proceedings of the 1st ACM Workshop on Wireless Multimedia Networking and Performance Modeling 2005
DOI: 10.1145/1089737.1089759
|View full text |Cite
|
Sign up to set email alerts
|

Performance evaluation of video streaming with background traffic over IEEE 802.11 WLAN networks

Abstract: There is an increasing demand for multimedia streaming applications over WLAN networks. MPEG-4 and H.264 are compression standards targeted at high-quality streamed multimedia services over wireless best-effort IP networks. However, the dynamic nature of wireless networks in terms of fluctuating bandwidth and time-varying delays makes it difficult to provide good quality streaming under such constraints. Multimedia streaming applications are a demanding and challenging service to deliver over wireless networks… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 10 publications
0
22
0
Order By: Relevance
“…2.1, to act friendly between both TCP applications and multicast applications. Those scenarios use background traffics [22], [23] and DropTail queue management, which is used by a typical router for managing incoming and outgoing packets in the buffers [24]. In addition, we proposed a set of mechanisms such as a simple class for creating a static wired network topology that can be used in NS2 simulation, providing various data rates with background traffics, a simple class of creating static wired network topology, various scenarios to represent the real internet environment.…”
Section: Contributionmentioning
confidence: 99%
“…2.1, to act friendly between both TCP applications and multicast applications. Those scenarios use background traffics [22], [23] and DropTail queue management, which is used by a typical router for managing incoming and outgoing packets in the buffers [24]. In addition, we proposed a set of mechanisms such as a simple class for creating a static wired network topology that can be used in NS2 simulation, providing various data rates with background traffics, a simple class of creating static wired network topology, various scenarios to represent the real internet environment.…”
Section: Contributionmentioning
confidence: 99%
“…They found the smaller the MTU packet size set in the hint track, the greater the access bandwidth required, and reducing the Iframe frequency only increases little bandwidth gains. They investigated the performance of video streaming with different background traffic in another paper [18], using the same research approach. Ikkruthy et al reported in [19] that there is a trade-off between packet sizes and the amount of information lost.…”
Section: Related Workmentioning
confidence: 99%
“…Among the most significant are low delivery rates, high error rates due to media characteristics, contention between stations for access to the medium, back-off mechanisms, collisions, signal attenuation with distance, signal interference, etc. Multimedia applications, in particular, impose onerous resource requirements on bandwidth constrained WLAN networks [2,3]. Under these conditions it is difficult to provide any Quality of Service (QoS) guarantees.…”
Section: Introductionmentioning
confidence: 99%